Unraveling Interactions between the Microbiome and the Host Immune System To Decipher Mechanisms of Disease - Catherine A. Lozupone (American Society for Microbiology, 2018)
ABSTRACT In recent years, there has been a deluge of papers linking altered microbiome compositions to a myriad of diseases. Mechanistic insight into microbial drivers of disease phenotypes is essential for translation to novel therapies. A key mechanism by which microbes influence health is immune modulation by components of their capsule and cell envelope and their metabolites. A major research focus of my laboratory is to gain mechanistic insight into which microbes modulate host immunity generally and in the context of disease. Using 16S rRNA-targeted sequencing, we have established associations between gut microbiome composition and immune-modulated disease phenotypes in diseases such as graft-versus-host disease in cancer patients undergoing stem cell transplantation. By integrating omics and computational approaches with laboratory experiments, we have expanded knowledge of mechanisms used by host-associated microbes to dampen inflammatory responses. This work has promise for development of novel microbiome-targeted therapeutics.